A Highly Photostable Near‐Infrared Labeling Agent Based on a Phospha‐rhodamine for Long‐Term and Deep Imaging. (16th July 2018) - Grzybowski, Marek; Taki, Masayasu; Senda, Kieko; Sato, Yoshikatsu; Ariyoshi, Tetsuro; Okada, Yasushi; Kawakami, Ryosuke; Imamura, Takeshi; Yamaguchi, Shigehiro
Abstract: Various fluorescence microscopy techniques require bright NIR‐emitting fluorophores with high chemical and photostability. Now, the significant performance improvement of phosphorus‐substituted rhodamine dyes (PORs) upon substitution at the 9‐position with a 2, 6‐dimethoxyphenyl group is reported. The thus obtained dye PREX 710 was used to stain mitochondria in living cells, which allowed long‐term and three‐color imaging in the vis‐NIR range. Moreover, the high fluorescence longevity of PREX 710 allows tracking a dye‐labeled biomolecule by single‐molecule microscopy under physiological conditions. Deep imaging of blood vessels in mice brain has also been achieved using the bright NIR‐emitting PREX 710‐dextran conjugate.